Experience with students from an unlicensed university: intervention effects on their creative thinking - Soto Hidalgo, Cinthya Virginia (2019)
We carry out a pedagogical intervention in the development of the creative thinking skills of fifth-cycle students in the university population. The research was applied, quasi-experimental. We propose to reinforce and influence moral values such as students' self-esteem and confidence; in order to highlight his creative abilities in four audiovisual productions divided into two television magazine programs and two short films aimed at social responsibility. We formed a sample of 44 students from a total population of 1281 from a private university in Lima. We structured the experiment by a control group and an experimental group with an amount of 22 students each and divided into groups of 5 or 6 work teams to develop the Torrance Creative Thought Questionnaire (TTCT). The control group obtained an apprenticeship with basic tools, unlike the experimental group in which workshops with technological tools and group dynamics were implemented during 16 sessions. We show the positive influence of the program in which students developed their creativity.